2022
DOI: 10.1097/pai.0000000000001023
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Inflammatory Cell Infiltration and Expression of STAT6 in the Lungs of Patients With COVID-19: An Autopsy Study

Abstract: Background: Severe acute respiratory syndrome coronavirus 2 causes diffuse alveolar damage (DAD), lymphocyte infiltration in the lungs and a cytokine storm. In this study we examined inflammatory cell infiltrates and the expression of signal transducer and activator of transcription (STAT) 6 in the lungs of patients with coronavirus disease 2019 (COVID-19).Methods: Eighteen COVID-19 autopsy cases, 9 non-COVID cases with DAD, and 11 controls without lung diseases were included. Immunostainings for STAT6, CD3, C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Pathomorphological studies of the lungs of those patients who died from COVID-19 showed the presence of pneumocytes, CD68+ macrophages, and CD3+ T cells with the activation of STAT6 expression in the inflammatory infiltrates [24]. Patients who died from COVID-19 showed a significant increase in CD4, CD68, and CD138 [25].…”
Section: Discussionmentioning
confidence: 99%
“…Pathomorphological studies of the lungs of those patients who died from COVID-19 showed the presence of pneumocytes, CD68+ macrophages, and CD3+ T cells with the activation of STAT6 expression in the inflammatory infiltrates [24]. Patients who died from COVID-19 showed a significant increase in CD4, CD68, and CD138 [25].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with lethal COVID-19 associated with macrophage counts of >130/High Power Field (HPF) showed shorter survival time in an autopsy cohort studied by Cao W et al [40].…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that viral exposure may promote inflammation and cell permeability causing immune cell infiltration that exacerbates disease and can cause ARDS or viral pneumonia [12] . A study using immunostained lung samples from patients with diffuse alveolar damage (DAD) as a result of COVID-19 showed a significant increase in the number of pneumocytes, macrophages and CD3+ T cells compared to healthy controls and non-DAD-COVID patients [13] . An increased presence of macrophages and fewer CD8+ T cells were further associated with poor outcomes in all COVID-19 patients suggesting a role between the overactivated innate immune system and disease exacerbation [14] .…”
Section: Cardiovascular Complications In the Lungsmentioning
confidence: 99%